ALARM PENDETEKSI KEBAKARAN PADA KABEL TRAY DI PEMBANGKIT LISTRIK TENAGA UAP PT. INDONESIA POWER UBP SURALAYA - , MOHAMAD ANGGI MULYONO; , Ir. Sri Lestari, M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In steam power plant (power plant) contained powder coal fly, and sometimes accumulate on the sidelines of the cable tray or in some other place. Sometimes the powder coal fly comes from the burner, where the burning of coal. Coal is carbon compounds that retain heat and can ignite at any time by itself, so it can be dangerous and result in a fire at the places at the point of generation, especially on cable tray which is a power cable from the boiler and the mile (the place grinding coal). Fires can result in generating units be derated even trip units. It required a protection that can detect burning coal powder. Cable fire protection system using relay control and sensor linear heat detector (LHD). Detection of burning coal powder using the LHD-type EPC sensor 68oC and will be shown on the indicator panel cable tray which contained burning coal powder.